Virtual Computed Tomography Colonography: Evaluation of 2D and Virtual 3D Image Quality of Sub-mSv Examinations Enabled by Third-generation Dual Source Scanner Featuring Tin Filtering - Seuß, Hannes; Janka, Rolf Matthias; Hammon, Matthias; Uder, Michael; Dankerl, Peter; Cavallaro, Alexander Josef (Academic Radiology, 2018)
RATIONALE AND OBJECTIVES: To evaluate two- and three-dimensional (2D and 3D) image quality of sub-milliSievert (mSv) computed tomography (CT) colonography utilizing a third-generation dual source CT scanner featuring a tin filter. METHODS: We retrospectively evaluated 26 consecutive patients who underwent third-generation dual source CT colonography, nine with the standard-dose clinical-scan protocol (SDP) and 17 with a low-dose protocol (LDP) featuring a tin filter. Radiation dose was evaluated by volume computed tomography dose index (CTDIvol), dose length product (DLP), effective dose (E), and size-specific dose estimate. Objective image quality was evaluated utilizing signal-to-noise ratio (SNR) derived from standardized placed regions of interest on the transverse 2D images and the ratio of SNR/CTDIvol (normalized SNR). Two radiologists in consensus assessed subjective image quality of the virtual 3D images. RESULTS: There were no significant differences in subjective image quality (P = .661). All examinations were rated "excellent" or "good" for diagnostic confidence. The mean total for DLP/E was 143.4 ± 29.8 mGy/3.00 ± 0.40 mSv in the SDP and therefore significantly higher than in the LDP with 36.9 ± 8.7 mGy/0.75 ± 0.16 mSv (P < .001). The SNR was 8.9 ± 2.1 in the SDP and 4.9 ± 0.8 in the LDP. CONCLUSIONS: Third-generation dual source CT featuring a tin filter enables consistent sub-mSv colonography without substantially impairing image quality.
EVALuna2:34692